Ride to Modernity : The Bicycle in Canada, 1869-1900. - Norcliffe, Glen. (Toronto : University of Toronto Press, 2001)
An examination how the bicycle as a symbol of modernity and social status fits into the larger picture of change and progress in a period of dramatic economic, social, and technological flux.
Intro -- Contents -- Illustrations -- Preface -- 1 Modernity and the Bicycle -- 2 The Bicycle Carrier Wave -- 3 Modern Manufacturing: From Artisanal Production to Mass Production -- 4 Bells and Whistles: The Bicycle Accessory Industry -- 5 Bad Roads, Good Roads -- 6 The Cycling Crowd: Modern Life on Wheels -- 7 Larger Spaces and Visible Places -- 8 Pedaller's Progress: The Bicycle and Modernity -- Notes -- Select Bibliography -- Illustration Credits -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- K -- L -- M -- N -- O -- P -- R -- S -- T -- V -- W -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Bicycles-Canada-History-19th century; Cycling-Canada-History-19th century; Cycling-Social aspects-Canada.; Bicycle industry-Canada-History-19th century; Electronic books